2009
DOI: 10.1021/ja809419f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simple Ribozymic Aminoacylation Using Three Conserved Nucleotides

Abstract: Selection-amplification finds new RNA enzymes (ribozymes) among randomized RNAs with flanking unvaried sequences (primer complements). Precise removal of 3′-primer before reaction selected aminoacylation from PheAMP in 3 cycles, yielding active RNAs (k cat = 12-20 min -1 ) using only three conserved nucleotides, acting independently of divalent ions. This unusually simple RNA active site encouraged study of the reaction via molecular mechanics-based free energy minimization. On this basis, we suggest a chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 34 publications
4
84
0
2
Order By: Relevance
“…In addition, chemically capable RNAs can be very small. A pentaribonucleotide ribozyme suffices to perform highly regiospecific aminoacyl transfer (Chumachenko et al 2009;Yarus 2011b). RNAs as small as two nucleotides have chemical phenotypes, even today (Yarus 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chemically capable RNAs can be very small. A pentaribonucleotide ribozyme suffices to perform highly regiospecific aminoacyl transfer (Chumachenko et al 2009;Yarus 2011b). RNAs as small as two nucleotides have chemical phenotypes, even today (Yarus 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should act in trans, and should use universal biological, water-soluble substrates. Previously isolated ribozymes employ appropriate substrates [amino acids activated as acyladenylates (6,12)], but are not true enzymes, as they are self-aminoacylators modified by their own reaction. Other ribozymes aminoacylate RNA with turnover; however, the amino acids must be activated as cyanomethyl, 3,5-dinitrobenzyl, or p-chlorobenzyl esters (8,13), and hence they do not facilitate the biological reaction.…”
mentioning
confidence: 99%
“…1A) presented the intriguing possibility of very simple aminoacyl transfer (6). Mutational analyses as well as molecular dynamics and energy minimization of the reactants suggested a tiny active center consisting of only three essential nucleotides-a 3 0 -terminal U, and a 5 0 -GU-3 0 sequence in a loop apposed to the unpaired 3 0 -terminal U.…”
mentioning
confidence: 99%
“…16 Other ribozymes that catalyze cis-aminoacylation or trans-aminoacylation on the 3¤-end of RNA in the presence of Phe-AMP (Phe: phenylalanine) were also generated. 12,17 Although the above ribozymes partly mimic the function of ARSs, they were unable to charge onto tRNA. Bessho et al have reported an acyl-transferase ribozyme Figure 1.…”
Section: Rna-acylation Ribozymes Flexizymesmentioning
confidence: 99%